Solvent‐Independent Molecular Weight Determination of Polymers Based on a Truly Universal Calibration - Voorter, Pieter‐Jan; McKay, Alasdair; Dai, Jinhuo; Paravagna, Olga; Cameron, Neil R.; Junkers, Tanja (Angewandte Chemie International Edition, 2022)
Diffusion‐ordered NMR spectroscopy (DOSY) allows for accurate molecular weight calibration and determination that can be corrected for solvent influences. Polystyrene and poly(ethylene glycol) standards have been used to calibrate DOSY diffusion data for a variety of solvents, showing a high correlation of data when the bulk viscosity of the solvent is accounted for following the Stokes–Einstein equation. In this way, a type of universal calibration is introduced that allows for determinations of average molecular weight that are at least as accurate as those of traditional size‐exclusion chromatography (SEC), if not better. Further, we demonstrate that DOSY calibrations can be used between laboratories, hence removing the need for individual calibration of setups as currently done. A universal calibration curve for molecular weight determination is presented. Diffusion coefficients of poly(styrene) and poly(ethylene glycol) standards are measured via diffusion‐ordered NMR spectroscopy. These diffusion/molecular weight relationships are calibrated to be solvent‐independent. This universal calibration creates a novel platform wherein molecular weights of unknown polymers can be found using the universal calibration curve independent of what solvent is used.